Визначення типу дизеля при ремоторизації тепловозів М62 - Ковалець, Юрій Юрійович; Kovalets, Yurii Yuriiovych (Національний університет "Львівська політехніка", 2024)
Тепловози типу М62 перестали випускатись луганським тепловозобудівним заводом ще в минулому столітті. Термін їх експлуатації перевищує встановлені норми і сягає більше тридцяти років. При цьому дизелі типу 14Д40 морально і технічно застарілі і вже давно не випускаються заводом-виробником. Тому експлуатація цих локомотивів визиває зниження коефіцієнта готовності парку і різке зростання експлуатаційних витрат на виконання йому різних ремонтних робіт. Вирішення даної проблеми повинно носити комплексний характер і включати, як оновлення тепловозів зразками нового покоління, так і модернізацію існуючих локомотивів з продовженням терміну їх експлуатації. Такий підхід дозволить ліквідувати кризу залізничної галузі в частині тягового рухомого складу. Однією з умов її реалізації є прийняття комплексної державної програми управлінням інвентарним парком тягового рухомого складу в частині модернізації локомотивів. Тому у кваліфікаційній роботі вирішується актуальна задача визначення типу модернізації тепловозу М62 новим раціональним дизелем. Об’єкт дослідження – технічна експлуатація магістрального тепловозу М62. Предмет дослідження – методи оцінки технічного рівня магістральних тепловозів та визначення їх основних техніко-економічних показників. Мета дослідження – визначити тип дизеля для раціональної ремоторизації тепловозів типу М62. За результатами кваліфікаційної роботи виконано такі задачі досліджень: - проведено аналіз підходів до модернізації тепловозів типу М62; - проведено аналіз існуючого стану тепловозів М62; - визначено технічний рівень тепловозів М62 з дизелями різних типів та визначено тип дизелю для раціональної ремоторизації локомотива; - розраховані основні техніко-економічні показники тепловоза з новим дизелем. Встановлено, що тепловоз являється одним із найбільш розповсюджених вантажних локомотивів виробництва луганськтепловоз в Україні та Європі. Хоча на даний момент він морально та технічно застарів, але за рахунок міцної рами може пройти модернізацію з продовженням строку служби. Багато власників даного тепловозу робили йому модернізацію різними типами силових установок, що показало доцільність їх використання. Методом вагових коефіцієнтів був вибраний тип дизеля для модернізації тепловозу для залізниць України. Магістральний тепловоз з дизелем EMD для умов експлуатації в нашій країні з врахуванням регіону, має найкращі показники. Розрахунок технічних характеристик тепловоза з даним дизелем підтвердив заявлені значення розробниками. Тому проведення тепловозів М62 цими дизелями являється доцільним для наших залізниць.

Diesel locomotives of the M62 type ceased to be produced by the Luhansk Diesel Locomotive Plant in the last century. Their service life exceeds the established norms and reaches more than thirty years. At the same time, diesel engines of the 14D40 type are morally and technically obsolete and have not been produced by the manufacturing plant for a long time. Therefore, the operation of these locomotives causes a decrease in the availability coefficient of the fleet and a sharp increase in operating costs for performing various repairs on it. The solution to this problem should be comprehensive and include both the renewal of diesel locomotives with new generation models and the modernization of existing locomotives with the extension of their service life. Such an approach will eliminate the crisis in the railway industry in terms of traction rolling stock. One of the conditions for its implementation is the adoption of a comprehensive state program for managing the inventory fleet of traction rolling stock in terms of locomotive modernization. Therefore, the qualification work solves the urgent problem of determining the type of modernization of the M62 diesel locomotive with a new rational diesel engine. Object of the research – technical operation of the M62 mainline diesel locomotive. Subject of the research – methods for assessing the technical level of mainline diesel locomotives and determining their main technical and economic indicators. Purpose of the research – determine the type of diesel engine for rational remotorization of diesel locomotives of the M62 type. According to the results of the qualification work, the following research tasks were completed: - an analysis of approaches to the modernization of diesel locomotives of the M62 type was carried out; - an analysis of the current state of diesel locomotives of the M62 type was carried out; - the technical level of diesel locomotives of the M62 type with diesel engines of various types was determined and the type of diesel engine for rational remotorization of the locomotive was determined; - the main technical and economic indicators of a diesel locomotive with a new diesel engine were calculated. It was established that the diesel locomotive is one of the most common freight locomotives manufactured by Luhanskteplovoz in Ukraine and Europe. Although at the moment it is morally and technically outdated, due to its strong frame it can undergo modernization with an extension of its service life. Many owners of this diesel locomotive have modernized it with different types of power plants, which has shown the feasibility of their use. The type of diesel engine for the modernization of the diesel locomotive for the railways of Ukraine was selected using the weight coefficient method. The mainline diesel locomotive with EMD diesel engine for operating conditions in our country, taking into account the region, has the best performance. Calculation of the technical characteristics of the locomotive with this diesel engine confirmed the values declared by the developers. Therefore, the operation of M62 diesel locomotives with these diesel engines is advisable for our railways.
Determining the type of diesel engine when remotorizing M62 diesel locomotives
Keywords: 6.273.00.02; тепловоз М62; модернізація; ремоторизація; дизель; технічний рівень; технічні показники тепловозу; diesel locomotive M62; modernization; remotorization; diesel; technical level; technical performance of the diesel locomotive